2022
DOI: 10.1159/000522132
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine System: Insights between Kidney and Brain

Abstract: BACKGROUND: Chronic kidney disease (CKD) is one of the most common diseases in adult age and it is typical of older adults. Recent data suggest that almost half of the elders have CKD. It is now clear that CKD is accompanied, in the early stages, by cognitive impairment, together with depression and subtle abnormalities in motor control (such as gait and balance alterations). SUMMARY: Several data suggest a link between brain dopamine and kidney diseases. Metabolic syndrome and diabetes can affect dopamine neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 177 publications
2
2
0
Order By: Relevance
“…Brain disorders were the most prevalent among the significant relationships identified (23/62, mental and behavioral disorders (14) and diseases of the nervous system (9)), followed by endocrine, nutritional and metabolic diseases (18/62) ( Table S5 ). These findings aligned with ongoing research on the complex interplay between the brain and abdominal organs, such as the brain-gut connection 5658 , brain-kidney connection 59,60 , and brain-liver connection 61 . Specifically, Alzheimer’s disease and dementia were linked to a reduction in liver volume and percent of liver fat (| β |>0.02, P < 1.28ξ10 −4 , 6/8 MR methods significant).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Brain disorders were the most prevalent among the significant relationships identified (23/62, mental and behavioral disorders (14) and diseases of the nervous system (9)), followed by endocrine, nutritional and metabolic diseases (18/62) ( Table S5 ). These findings aligned with ongoing research on the complex interplay between the brain and abdominal organs, such as the brain-gut connection 5658 , brain-kidney connection 59,60 , and brain-liver connection 61 . Specifically, Alzheimer’s disease and dementia were linked to a reduction in liver volume and percent of liver fat (| β |>0.02, P < 1.28ξ10 −4 , 6/8 MR methods significant).…”
Section: Resultssupporting
confidence: 76%
“…These findings corroborated ongoing research concerning the interplay between the brain and abdominal organs, such as the brain-gut connection [62][63][64] , brain-kidney connection 65,66 , and brain-liver connection 67 .…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 83%
“…DA is a neuromodulator that has the ability to diffuse away from the site of its release, activating receptors that are far from the terminal; this ability is called transmission volume [ 2 ]. In this sense, DA receptors have been identified in nonneuronal tissues, which has been related to their therapeutic potential in pathologies such as sepsis or septic shock, blood pressure, renal failure, diabetes, and obesity, among others [ 6 , 7 , 8 ]. In addition, it has been reported that DA and dopaminergic drugs such as bromocriptine, cabergoline, pramipexole, and ropinirole have shown anti-inflammatory and antioxidant functions in different kinds of cells, reducing reactive oxygen species (ROS) accumulation, preserving glutathione (GSH) and other antioxidant enzymes, and decreasing lipid peroxidation [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…When insulin function in the brain is compromised, it initiates cellular disturbances, resulting in pathological states. For example, MetS and DM can render dopaminergic neurons vulnerable [ 40 ] and affect dopamine neuron survival [ 41 ]. IR may lead to reduced expression of dopamine transporter proteins on the striatal surface, as demonstrated in animal models [ 42 ].…”
Section: Discussionmentioning
confidence: 99%